Trends Over Time in the Risk of Adverse Outcomes Among Patients With Severe Acute Respiratory Syndrome Coronavirus 2 Infection. (10th May 2021) - Ioannou, George N; O'Hare, Ann M; Berry, Kristin; Fan, Vincent S; Crothers, Kristina; Eastment, McKenna C; Locke, Emily; Green, Pamela; Shah, Javeed A; Dominitz, Jason A
Abstract: Background: We aimed to describe trends in adverse outcomes among patients who tested positive for severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) between February and September 2020 within a national healthcare system. Methods: We identified enrollees in the national United States Veterans Affairs healthcare system who tested positive for SARS-CoV-2 between 28 February 2020 and 30 September 2020 (n = 55 952), with follow-up extending to 19 November 2020. We determined trends over time in incidence of the following outcomes that occurred within 30 days of testing positive: hospitalization, intensive care unit (ICU) admission, mechanical ventilation, and death. Results: Between February and July 2020, there were marked downward trends in the 30-day incidence of hospitalization (44.2% to 15.8%), ICU admission (20.3% to 5.3%), mechanical ventilation (12.7% to 2.2%), and death (12.5% to 4.4%), which subsequently plateaued between July and September 2020. These trends persisted after adjustment for sociodemographic characteristics, comorbid conditions, documented symptoms, and laboratory tests, including among subgroups of patients hospitalized, admitted to the ICU, or treated with mechanical ventilation. From February to September, there were decreases in the use of hydroxychloroquine (56.5% to 0%), azithromycin (48.3% to 16.6%), vasopressors (20.6% to 8.7%), and dialysis (11.6% to 3.8%) and increases in the use of dexamethasone (3.4% to 53.1%), other corticosteroids (4.9% to 29.0%), and remdesivir (1.7% to 45.4%) among hospitalized patients. Conclusions: The risk of adverse outcomes in SARS-CoV-2–positive patients decreased markedly between February and July, with subsequent stabilization from July to September. These trends were not explained by changes in measured baseline patient characteristics and may reflect changing treatment practices or viral pathogenicity. Abstract : The risk of adverse outcomes in patients with severe acute respiratory syndrome coronavirus 2 infection declined substantially from February to July 2020, and subsequently plateaued from July to September 2020. These trends may reflect changing treatment practices or viral pathogenicity.